RATIFICATION OF SEANWFZ: ORIGIN OF THE COMMON IDEA AND ITS CONSISTENCY - Ahmad Anwar (Jurusan Ilmu Hubungan Internasional, 2018)
Nuclear as a weapon of mass destruction cannot be separated from the world political agenda. Various international agreements as a control mechanism on this issue are followed by the establishment of some security regimes for nuclear weapons-free areas. One of them is South East Asia Nuclear Weapons Free Zone (SEANWFZ) in Southeast Asia. Established in 1995, the treaty was finally ratified by ten ASEAN member states. This paper examines the political history of why ASEAN member states were willing to ratify SEANWFZ. By using the constructivism approach, the study underlines that the aspects of ideas and shared concerns on regional security have become vision in encouraging the ratification of the treaty. Moreover, understanding the political history could give the explanation of contemporary significance of the treaty, mainly it is in line with the idea to prevent military exercise by great powers in the region.